Kajian Living Hadis: Tradisi Shalawat Boban pada Majelis Pengajian Kampung Godang Bangkinang - Firman, Firman; Arsyi, Muhammad (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
Shalawat is an act of worship that is easy to practice but highly beloved by Allah SWT, as reflected in various verses of the Qur'an and Hadith, which promise abundant rewards for those who recite it. Therefore, Shalawat is an act of devotion recommended for daily practice. One example of this practice can be seen in the Shalawat Boban tradition, performed by the women in the Majelis Pengajian (study group) in Kampung Godang, Bangkinang, with its unique characteristics. This study aims to examine the living values of Hadith in the Shalawat Boban tradition and its interpretation within the context of the community. Employing a field research method with a Living Hadith approach and phenomenology, this research is descriptive, qualitative, and inductive. The findings of this study conclude that the tradition developing in the life of the Kampung Godang community is a phenomenon of Living Hadith, based on religious principles that serve as the foundation and guide for these activities. Additionally, this study group has significant meaning, not only as a spiritual worship practice but also as a means to strengthen social bonds and solidarity within the community.